2006
DOI: 10.1002/adma.200501802
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Patterning of Molecular Glasses Using Supercritical Carbon Dioxide

Abstract: Continuous advances in the semiconductor and microfabrication industries are based on formation of increasingly smallscale devices. Photolithography, the process by which small features are patterned into a thin organic film (photoresist) by UV or electron-beam (e-beam) irradiation, is the principle process by which small features are formed. To produce the planned sub-50 nm features required for next-generation devices remains a challenge due to the increased importance of pattern perfection and elimination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…[48,53] sc CO 2 development for the negative type molecular-glass photoresist has been suggested as a new process step to alleviate pattern collapse in densely packed, high-aspect-ratio structures. [54] However, supercritical drying of some positive photoresists resulted in the formation of cracks. Replacement of water with pentane or hexane, which have a lower surface tension (73.05 mN m -1 , 13.72 mN m -1 , and 18.43 mN m -1 for water, pentane, and hexane respectively at 20°C [44,55] ) has been proposed as an alternative method.…”
Section: Preventing Pattern Collapsementioning
confidence: 99%
“…[48,53] sc CO 2 development for the negative type molecular-glass photoresist has been suggested as a new process step to alleviate pattern collapse in densely packed, high-aspect-ratio structures. [54] However, supercritical drying of some positive photoresists resulted in the formation of cracks. Replacement of water with pentane or hexane, which have a lower surface tension (73.05 mN m -1 , 13.72 mN m -1 , and 18.43 mN m -1 for water, pentane, and hexane respectively at 20°C [44,55] ) has been proposed as an alternative method.…”
Section: Preventing Pattern Collapsementioning
confidence: 99%
“…In the last decade it has been shown that small molecules with glassy properties, so called molecular glasses, can serve as resist materials as well, [2][3][4][5][6] and recently, thermally stable star-shaped molecules with high glass transition temperatures have been introduced. [7,8] Usually, the necessary resist films needed for high resolution imaging are deposited by casting from solution via spin coating or doctor blading techniques, depending on application. One of the disadvantages of these solution-based methods is that solvents may contain dust or other high boiling residues, which causes a rougher surface or leaves impurities in the film.…”
Section: Introductionmentioning
confidence: 99%
“…Fully t-BOC-protected hexa(hydroxyphenylbenzene)-mp was developed in scCO 2 upon e-beam exposure to produce 50 nm negative tone feature sizes with a 3:1 aspect ratio. [34] Because of behavior as a one phase fluid, scCO 2 has proven [34] to alleviate pattern collapse in densely packed, high-aspect-ratio resist features. Recent work also reports that calix [4]resorcinarene derivatives up to 2000 g mol À1 can be developed in scCO 2 with very high dissolution rates.…”
Section: Development In Supercritical Carbon Dioxidementioning
confidence: 99%